Causal effects of metabolites on malignant neoplasm of bone and articular cartilage: a mendelian randomization study - Du, Yongwei; Xiao, Xiqiu; Liu, Fuping; Zhu, Wenqing; Mo, Jianwen; Liu, Zhen (Frontiers in Genetics, 2025)
ObjectivePrevious research has demonstrated that metabolites play a significant role in modulating disease phenotypes; nevertheless, the causal association between metabolites and malignant malignancies of bones and joint cartilage (MNBAC)has not been fully elucidated.MethodsThis study used two-sample Mendelian randomization (MR) to explore the causal correlation between 1,400 metabolites and MNBAC. Data from recent genome-wide association studies (GWAS) involving 8,299 individuals were summarized. The GWAS summary data for metabolites were acquired from the IEU Open GWAS database, while those for MNBAC were contributed by the Finnish Consortium. We employed eight distinct MR methodologies: simple mode, maximum likelihood estimator, MR robust adjusted profile score, MR-Egger, weighted mode, weighted median, MR-PRESSO and inverse variance weighted to scrutinize the causal association between metabolites engendered by each gene and MNBAC. Consequently, we evaluated outliers, horizontal pleiotropy, heterogeneity, the impact of single nucleotide polymorphisms (SNPs), and adherence to the normal distribution assumption in the MR analysis.ResultsOur findings suggested a plausible causative relationship between N-Formylmethionine (FMet) levels, lignoceroylcarnitine (C24) levels, and MNBAC. We observed a nearly significant causal association between FMet levels and MNBAC within the cohort of 1,400 metabolites (P = 0.024, odds ratio (OR) = 3.22; 95% CI [1.16–8.92]). Moreover, we ascertained a significant causal link between levels of C24 and MNBAC (P = 0.0009; OR = 0.420; 95%CI [0.25–0.70]). These results indicate a potential causative relationship between FMet, C24 level and MNBAC.ConclusionThe occurrence of MNBAC may be causally related to metabolites. This might unveil new possibilities for investigating early detection and treatment of MNBAC.